Sightings of cetaceans in the waters of Yuzhny Sea Port (Hryhorivsky estuary, Black Sea) in 2015–2016 - Savenko, O.; Ivanchikova, J.; Hulak, B.; Derkacheva, T. (Праці теріологічної школи, 2016)
The use of transformed coastal ecosystems by the Black Sea cetaceans is an important, but little studied issue. In 2015–2016, coastal visual observations of cetaceans were conducted in the waters of Yuzhny Sea Port. The area was regularly used by common dolphins (they were sighted in 24 days of 64) and also by harbour porpoises (7 sightings). Group sizes of the common dolphins reached up to 25 individuals (Median = 7), and of the harbour porpoises — up to 5 (Median = 4); calves and juveniles were present in most groups. The primary behaviour of cetaceans was feeding. Because of significant concentrations of fish in Hryhorivsky Estuary, the area of Yuzhny Sea Port is an important habitat for the Black Sea cetaceans.